Article RETRACTED due to manipulation by the authors Development of an endurance training model in athletic performance: a case study on long distance running in Indonesia - Risnawati Risnawati; Hidayat Humaid; Iman Sulaiman; Ali Muhaimin; Azizil Fikri; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to create innovative and effective endurance training materials tailored for long-distance runners aged 15-18. Utilizing the research and development (RnD) approach with the Borg and Gall model, the study incorporates feedback from expert validators and athletes along with their coaches from Sorong, West Papua. The research procedure encompasses ten stages, starting with problem identification and culminating in the implementation of the final product, involving 80 athletes. These stages include initial analysis, planning, initial product development, preliminary field testing, primary product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination and implementation. The involvement of both experts and practitioners ensures the training materials are theoretically sound and practically applicable. Data analysis was conducted using SPSS version 21, employing a normality test, a homogeneity test, and a paired-sample t-test to ensure the reliability and validity of the findings. The normality test confirmed the data followed a normal distribution, while the homogeneity test ensured the sample groups were comparable. The paired-sample t-test results indicated the newly developed book-based endurance training model significantly enhanced athletes' performance (p-value 0.000), showing a more substantial improvement in training outcomes compared to conventional methods (p-value 0.014). This improvement is attributed to the structured and comprehensive nature of the training materials, which include interactive elements and technology integration, making the training process more engaging and effective for young athletes. In conclusion, adopting interactive and technology-based training models can significantly aid in developing endurance skills in young long-distance runners, addressing specific needs and optimizing their training regimen.